Insights and Experiences from the BioCarbon Fund Emission Reductions Projects in the Land-Use Sector : An Overview - World Bank (World Bank, Washington, DC, 2020)
Housed within the climate funds management unit (SCCFM) of the climate change group (CCG) in the World Bank, the biocarbon fund (BioCF), a public-private initiative, has pioneered results-based payments for emission reductions (ERs) from the land-use sector. The challenges can be daunting: dedicated and continuous engagement by stakeholders, and adequate financial and technical capacity are essential in order to ensure that project objectives are met, and benefits can be realized. This report, therefore, looks back at the 10 to 15 years of implementation of BioCF projects, and their groundbreaking experience under both the compliance (CDM) and voluntary (VCS) standards. Among these projects are concrete, real-world examples of both the successes and challenges faced in monitoring, reporting, verification (MRV), and communicating project objectives and results to stakeholders, and distributing benefits. This report is based on a desk review of project documents (including monitoring and verification reports available on the CDM and VCS project pages); World Bank project documents; interviews with World Bank staff involved in the preparation and supervision of the projects, and BioCF administration; and some of the implementing agencies or project entity (PEs). This analysis includes examination of the issues that have impacted BioCF projects throughout the project life cycle. The relationship of how these various issues have impacted implementation and ER delivery. The lessons learned and collected in this study have helped to identify a wide range of issues and challenges, as well as good practices on various aspects of ER operations, which can lead to either the success or failure of these initiatives.